Environmental Crime and Communication to the Public in China - Alexander Shytov (2018)
© 2016, Journal of Chinese Political Science/Association of Chinese Political Studies. In this article, the issue of communication in Chinese environmental criminal law is examined in relation to whether it is understandable to the public or not. It is concluded that Chinese environmental criminal law is ambiguous. It is argued that poor enforcement of criminal environmental law is partly due not only to the failure of the lawmakers to make clear rules but also to the failure of communicating important moral and aesthetic values to the public so necessary for effective protection of the environment. It is affirmed that along with the rules of behaviour, law must also communicate values. The Chinese history has its own rich pro-environmental ethical tradition of Confucianism, Taoism, and Buddhism which must be utilized to address all aspects of environmental protection including environmental crime issues. Legislation must be an educational tool which communicates vital moral values to the public. Environmental protection is one area where such communication is particularly important.